Chronic traumatic brain injury associated with boxing - Jordan, B. D. (Seminars in Neurology, 2000)
Chronic traumatic brain injury (CTBI) associated with boxing occurs in approximately 20% of professional boxers. Risk factors associated with CTBI include increased exposure (i.e., duration of career, age of retirement, total number of bouts), poor performance, increased sparring, and apolipoprotein (APOE) genotype. Clinically, boxers exhibiting CTBI will present with varying degrees of motor, cognitive, and/or behavioral impairments. The severe form of CTBI is referred to as dementia pugilistica. The diagnosis of CTBI is dependent upon documenting a progressive neurological condition that is consistent with the clinical symptomatology of CTBI attributable to brain trauma and unexplainable by an alternative pathophysiological process. Pathologically, CTBI shares many characteristics with Alzheimer's disease (i.e., neurofibrillary triangles, diffuse amyloid plaques, acetylcholine deficiency, and/or tau immunoreactivity). The mainstay of treatment of CTBI is prevention, however medications used in the treatment of Alzheimer's disease and/or parkinsonism may be utilized.